Effectiveness of a paraverterbral nerve block versus local portal blocks for laparoscopic closure of the nephrosplenic space: A pilot study. Issue 5 (28th May 2020) - Delli‐Rocili, Massimo M.; Cribb, Nicola C.; Trout, Donald R.; Thomason, Jeffrey J.; Valverde, Alexander
Abstract: Objective: To compare the effectiveness of a paravertebral nerve block vs local portal blocks for laparoscopic closure of the nephrosplenic space in standing sedated research horses. Study design: Randomized clinical trial. Animals: Twelve horses were randomly allocated to two groups ( n = 6 per group), paravertebral block of nerves T18, L1, and L2 or local blocks of the three laparoscopic portals. Methods: Horses were sedated with dexmedetomidine (4 μg/kg IV and constant rate infusion [CRI] of 2.5 μg/kg/h) and morphine (50 μg/kg IV and CRI of 30 μg/kg/h). According to group allocation, 20 mL of either lidocaine or saline was injected into each paravertebral nerve site or into each local portal site to facilitate laparoscopy for closure of the nephrosplenic space. The overall quality of sedation, analgesia, behavior exhibited during surgery, and ease to perform the surgery were blindly scored by using a visual analog scale (VAS). Results: Time to complete local anesthesia was similar for both blocks, and there was no difference in VAS scores between groups. Total duration of surgery was also similar between the paravertebral (79 ± 16 min) and local portal blocks (85 ± 25 min) groups. Conclusion: The paravertebral nerve block and the local portal blocks provided similar conditions during surgery and can be used interchangeably for closure of the nephrosplenic space. Clinical significance: The paravertebral nerve block can be readily performed and may be useful in surgical procedures.